Aggregation-induced emission enhancement in boron difluoride complexes of 3-cyanoformazanates. Issue 27 (29th June 2016) - Maar, Ryan R.; Gilroy, Joe B.
Abstract : Boron difluoride (BF2 ) complexes of 3-cyanoformazanates exhibit aggregation-induced emission enhancement in THF–water mixtures due to their severely twisted N -aryl substituents which restrict intramolecular motion and π stacking upon aggregation. Abstract : Boron difluoride (BF2 ) complexes of 3-cyanoformazanates exhibit aggregation-induced emission enhancement in THF–water mixtures due to their severely twisted N -aryl substituents which restrict intramolecular motion and π stacking upon aggregation.